Effect of water stress and AM fungi on the growth performance of pea - Jaya Thakur; Bharat Shinde (Hasanuddin University, 2020)
The study was conducted to determine the effect of arbuscular mycorrhizal (AM) fungi inoculation on growth of pea grown under water stressed pot culture conditions. Water stress was given to the pea plants after 30 days at the interval of 4, 8 and 12 days. The data was collected at an interval of 15 days. Three replicates of each set were maintained. . The mixture of AM fungi used for current experiment included the species of Acaulospora denticulata, A. gerdemannii, Glomus macrocarpum, G. maculosum, G. fasciculatum and Scutellospora minuta. The mycorrhizal plants have shown more shoot and root length as compared to the control plants. The height of shoot and root was significantly decreased with the increase in drought stress. Mycorrhizal plants with low water stress showed enhanced shoot and root length than high water stress. The mycorrhizal plants have shown more number of leaves than control plants during drought stress. The number of leaves significantly reduced with the increase in drought stress. The leaves produced by the control plants were comparatively smaller than those of mycorrhizal plants. The dry weight of root and shoot of both control and mycorrhizal plants decreased with the increase in water stress. Mycorrhizal plants showed more dry weight of shoot and root as compared to control plants. Plants inoculated with AM fungi produce more dry weight than the control plants. The fresh weight of both control and mycorrhizal plants has been decreased with the increase in water stress interval and also the fresh weight of root and shoot was observed higher in mycorrhizal plants as compared to those of control plants.